Competitive success of junior female alpine skiers in light of certain chosen tests of co-ordination - Dolenc, Maja (Kinesiologia Slovenica, 2001)
The objective of this investigation was to determine the mutual correlations between the three variables of co-ordination (ability for efficient resolution of space-related problems, ability for realising rhythmic structures and agility) and their individual correlations with the competitive success of junior female alpine skiers. The sample consisted of twenty-four junior female competitors in alpine skiing. To evaluate their co-ordination three tests were selected (polygon backwards, side-stepping, drumming). The criterion variable (competitive success) was the sum of points achieved in the competitions of the Radenska Cup. In the first phase of analysis, the Pearson correlation coefficients between the individual independent variables and their individual correlationswith the criterion were computed. The relations between the co-ordination space variables and success in alpine skiing were studied by multiple regression analysis. The mutual correlations between the co-ordination variables were statistically non-significant. The Pearson correlation coefficients with the criterion were statistically significant for sidestepping (r = -0.50) and polygon backwards (r = -0.43). Multiple regression analysis showed a statistically significant association (Multiple R = 0.56, Sig F = 0.05) between the predictors and the criterion, the independent variables explaining about 31% of the criterion variance.
Keywords: alpsko smučanje; koordinacija; mlajše deklice; raziskave; tekmovalna uspešnost